Prednisolone impairs embryonic and posthatching development and shell formation of the freshwater snail, Physa acuta. (17th June 2016) - Bal, Navdeep; Kumar, Anu; Du, Jun; Nugegoda, Dayanthi
Abstract: The aim of the present study was to investigate the lethal and sublethal effects of prednisolone exposure on the embryonic and posthatching stage of the freshwater snail, Physa acuta . The egg masses were exposed for 14 d to prednisolone concentrations ranging from 15.6 μg/L to 1000 μg/L. Treatment with prednisolone at 125 μg/L to 1000 μg/L resulted in significant decline in growth, survival, and heart rate, as well as notable abnormalities in embryonic development. Premature embryonic hatching was observed at lower concentrations of 31.25 μg/L and 62.5 μg/L, whereas delayed hatching was seen at concentrations from 125 μg/L to 1000 μg/L. To assess impacts of prednisolone exposure on the hatched juveniles, the drug exposure was extended for another 28 d. Impairment of shell development was noted in juveniles exposed to concentrations from 62.5 μg/L to 1000 μg/L at the end of 42 d, which resulted in thin and fragile shells. The thickness of shells in snails exposed to 1000 μg/L was significantly lower in comparison to those in the 15.6‐μg/L and control treatments. In addition, lower calcium concentration in shells of the exposed juvenile snails at treatments of 62.5 μg/L to 1000 μg/L consequently reduced their growth. The present study confirms that continuous exposure to prednisolone can result in deleterious effects on calcium deposition, resulting in shell thinning in the freshwater snail P. acuta . Environ Toxicol Chem 2016;35:2339–2348. © 2016 SETAC